2014
DOI: 10.4236/ajor.2014.44021
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Choice, Firm Performance and Channel Coordination in a Dual-Channel Distribution System

Abstract: The expanding role of the Internet in consumer purchasing activities has created substantial new opportunities accessing to end-consumers. More and more manufacturers are beginning to sell products to potential consumers directly online while continuing to sell through the traditional brick-and-mortar retailers, a phenomenon leading to intense channel competition and conflicts. Using game theory, this research examines the effect of market segments, consumer choice and the acceptance of direct online channels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
1
0
2
Order By: Relevance
“…La tendencia a establecer canales mixtos de distribución cambió las relaciones tradicionales entre fabricantes y minoristas [10] . Añadir un nuevo canal directo puede hacer sentir incómodos a los minoristas y hacer que éstos reaccionen, desatando una franca competencia que lleva a inevitables conflictos que atentan contra la cooperación y traen efectos negativos en las ganancias [11] . Los beneficios de implementar un doble canal de distribución y sus posibles consecuencias es lo que se plantea como elementos decisivos para inclinarse a abrir o no un nuevo canal directo on-line o quedarse únicamente con el canal de distribución tradicional que incluye minoristas.…”
Section: Marco Teóricounclassified
See 1 more Smart Citation
“…La tendencia a establecer canales mixtos de distribución cambió las relaciones tradicionales entre fabricantes y minoristas [10] . Añadir un nuevo canal directo puede hacer sentir incómodos a los minoristas y hacer que éstos reaccionen, desatando una franca competencia que lleva a inevitables conflictos que atentan contra la cooperación y traen efectos negativos en las ganancias [11] . Los beneficios de implementar un doble canal de distribución y sus posibles consecuencias es lo que se plantea como elementos decisivos para inclinarse a abrir o no un nuevo canal directo on-line o quedarse únicamente con el canal de distribución tradicional que incluye minoristas.…”
Section: Marco Teóricounclassified
“…El punto central es minimizar o evitar la competencia entre canales y evitar el conflicto. Se deben investigar las condiciones en las cuales un fabricante debería abrir un canal de distribución directo on-line dado que podría traer un enfrentamiento con el canal tradicional [11] , por lo que los métodos para disipar las preocupaciones de los minoristas son primordiales [19] . Teóricamente, si existe coordinación entre ambos actores, esto también podría traer ganancias para el minorista, reduciendo así la posibilidad de conflicto [20] .…”
Section: Figura 1 Estructura Del Canal Dual De Distribuciónunclassified
“…Altintas et al [10] studied a multiperiod model, with a buyer facing stochastic end-item demand and a supplier offering an all-units quantity discount to them, studied the supplier's profit as a function of their offered quantity-discount scheme (accommodating the buyer's optimal policy), and discovered a new phenomenon that was distinct and structurally different from the well-known bullwhip effect. Song et al [11] examined the effect of market segments, consumer choice, and the acceptance of direct online channels on firm performance and the whole system's profit. The analysis indicated that the addition of direct online channel did not necessarily harm the incumbent retailers.…”
Section: Literature Review and Research Purposementioning
confidence: 99%